Historical Land Use and Land Cover Change of Eastern Nepal: A Case of Dharan Sub-Metropolitan City (The Geographic Base, 2021)
Land use and land cover change (LUCC) has become an essential for monitoring and managing the natural resources, urban planning as well as sustainable development of any place. This study analyzes the historical LUCC during 1986-2020 of Dharan sub-metropolitan city (DSC) of Sunsari district, eastern Nepal. To analyze historical LUCC, LRMP (1986), ICIMOD (1990, 2000, 2010) and Google Earth Image (December, 2020) were used in the study. The results reveal the expansion of built-up areas by 500%, whereas agricultural land and forest cover decreased by 4% and6%, respectively, during the past 34 years. Mainly the growing built-up area encroached on the agricultural land, forest and river banks. The built-up area is expanded to the south-eastern, north-eastern and western direction from the core area. The built-up area is still likely to increase with high pace in the future, where need to give more attention to future possible urban hazards, urban pollutions and haphazard urbanization while making urban planning and policies.